SISTEM INFORMASI AKUNTANSI HARGA POKOK PRODUKSI DENGAN METODE ACTIVITY BASED COSTING PADA UKM UKIR JEPARA - Miftahurrohman Miftahurrohman; Moh Muthohir (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
The aim of this study is to design a production accounting information system for the determination of the cost of production that can help the SMEs Jepara carving in the determination of the cost of a product exactly. Information on the cost of a product is very important as a basis in determining the selling price of a product. so far the SMEs Jepara carving in determining the cost of a product is done by estimating the costs of production and often do not include a production cost that nominal little cost. So the cost of production does not reflect actual cost consumption. This can certainly cause the production cost to be undercost or uppercost. The approach in determining the cost of production using the method of ativity-based costing, activity-based costing method is the determination of the cost of a product based on activity. Research methods that Research method using Reseach and Development (R&D) method with prototype system development model. This study was conducted on SMEs carving Jepara. The result of this research is in the form of accounting information system product for determination of cost of production at SME Jepara carving which can assist in determination of cost of product. Implementation of the activity-based costing method as an approach in determining the cost of products is able to provide benefits that the charging over the cost can be more precise. Efficiency in costs can be obtained. The use of activity based costing method can also decrease the selling price of the product, so that Jepara carving SMEs will be better able to compete both for domestic market and international market.